Komitmen Organisasi Ditinjau Dari Status Pernikahan - Khairuddin Khairuddin (Mahesa Research Center, 2021)
This study aims to empirically determine the description of organizational commitment to MTs Al-Islamiyah Karang Anyar teachers. The sampling technique was carried out by total sampling technique and got 43 samples. The research instrument used was the organizational commitment scale. This type of research is quantitative research with descriptive and comparative models. The data analysis technique used is the one sample t-test. Researchers hypothesized that married teachers would tend to have higher organizational commitment than unmarried teachers. The results showed that the organizational commitment of the teachers was generally high. In accordance with the proposed hypothesis, it is said that there is a difference in organizational commitment between teachers who are married and teachers who are not married. The t-test results obtained were p = 0.000 (p <0.05). This shows that there is a significant difference. The empirical mean of married teachers are 100.06 and unmarried teachers are 90.54.